Multi-Agent-Based Simulation X International Workshop, MABS 2009, Budapest, Hungary, May 11-12, 2009 Revised Selected Papers - Tosto, Gennaro; Dyke Parunak, H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume contains a selection of the papers presented at the 10th International Workshop on Multi-Agent-Based Simulation (MABS 2009), a workshop co-located with the 8th International Conference on Autonomous Agents and Multiagent Systems (AAMAS 2009), which was held on May 10-15, 2009 in Budapest, Hungary.
Urban and Environmental Modelling -- Cumulative Effects and Emergent Properties of Multiple-Use Natural Resources -- Micro-scale Simulation of the Macro Urban Form: Opportunities for Exploring Urban Change and Adaptation -- Simulation of Economic Behaviour -- An Agent-Based Framework for Assessing the Cost of Committal Search in Supply Networks -- Does Cognitive Capacity Matter When Learning Using Genetic Programming in Double Auction Markets? -- A Multi-Agent System for Adaptive Production Networks -- Methods and Methodologies -- A Multi-environment Multi-agent Simulation Framework for Self-organizing Systems -- Software Development Process Simulation: Multi Agent-Based Simulation versus System Dynamics -- Agent-Based Simulations with Beliefs and SPARQL-Based Ask-Reply Communication -- Stigmergic Modeling of Hierarchical Task Networks -- Modelling of Social Phenomena -- The Impact of Naive Agents in Heterogeneous Trust-Aware Societies -- HUME1.0 - An Agent-Based Model on the Evolution of Trust in Strangers and Division of Labour -- Mentat: A Data-Driven Agent-Based Simulation of Social Values Evolution.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information systems; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Software Engineering; Information Systems Applications (incl.Internet).; Simulation and Modeling; User Interfaces and Human Computer Interaction